Thermodynamics guided design and processing of a WC/HEA cermet tool for high temperature friction stir welding - Supreeth Gaddam; Surekha Yadav; Amit Kishan Behera; Noriaki Arai; Zaynab Mahbooba; Shikhar Krishn Jha; Qiaofu Zhang; Rajiv S. Mishra (Materials & Design)
Friction stir welding (FSW) of high temperature materials such as ferrous alloys, Ti-alloys, and Ni-alloys is challenging due to the high costs, short tool lives, and limited availability of tool materials. Commercially available cermets such as WC/Co are relatively cost-effective, yet their performance is largely compromised by subpar high temperature properties of the Co binder. To address this issue, an integrated computational materials engineering (ICME) approach was applied to design a WC/HEA cermet with high entropy alloy (HEA) binder for better mechanical properties and high temperature performance. The WC/HEA cermet was fabricated by powder metallurgy route using mechanical alloying and mixing followed by spark plasma sintering (SPS). The SPS-sintered WC/HEA cermet possessed good room temperature hardness-fracture toughness synergy and hot hardness property. FSW tools were fabricated using the WC/HEA material and the tools were benchmarked against a high strength low alloy grade 50 (HSLA-50) steel. The tools performed with no observed chemical interaction with the workpiece material. The HSLA-50 material showed improved microstructure, hardness, and tensile properties post FSW. This study is the first proof-of-concept for the design, fabrication, testing, and evaluation of a novel cermet FSW tool material with low-cost and high-performance synergy for high temperature FSW application.